Introducing The Flipped Classroom To Pre-service Teachers During The Covid-19 Pandemic Era - Zohra Labed; Djamel Sebbah (The Journal of Studies in Language, Culture and Society, 2024)
The present paper intended to theoretically explore the strategy of flipped classroom. After experiencing the era of the COVID-19 pandemic and its consequences, it became paramount to rethink about other effective ways to teach higher education students. Particularly, we thought it vital to go through a pre-flipped classroom implementation training whereby the pre-service teachers at Oran Higher School of Education, Algeria, would get prepared psychologically to accept this new methodology of teaching as part of their educational process. In fact, one semester classes of second year British civilisation for English degree were flipped during the new academic year, 2020/2021, after the pandemic lockdown. Based on unstructured observations, we, the educators, could detect some strengths and weaknesses out of this experience. While the flipped classroom could raise some learners’ self-confidence, it was a source of demotivation for others as they had issues with the Internet connectivity. Yet, all the detected points would still be hypotheses that would need further research confirmation.